Депортаційні акції 1940-х років у національній пам’яті українців: стан та перспективи дослідження (за матеріалами наукового повідомлення на засіданні Президії НАН України 28 грудня 2022 р.) - Артимишин, Ю.З. (Вісник НАН України, 2023)
Простежено процес творення спогадів про міжнаціональний польсько-український конфлікт, депортацію та подальшу адаптацію переселених
осіб. Відтворено та проаналізовано збірний образ депортацій з українсько-польського прикордоння у 1944—1951 рр. в уявленнях переселенців та їхніх
нащадків. Досліджено співвідношення між різними рівнями ідентичності,
зокрема регіональною та національною. Розглянуто концепт малої батьківщини крізь призму колективної пам’яті. The process of creation of memories about inter-ethnic Polish-Ukrainian conflict as well as about deportation and further
adaptation is observed at three levels (personal and family level; level of deportees’ communities; level of regions
where displaced persons live). Collective image of deportations from the Ukrainian-Polish borderland in 1944—1951 as
well as of traumatic events, that preceded this process, in the views of displaced persons and their descendants is recreated,
and the inclusion of their experience in the historical memory of Ukraine is studied.
The oral and written memories of the deportees are analyzed in this work. It is established that in their collective
memory, the war, as a rule, began with the aggravation of the Polish-Ukrainian conflict in the Kholmshchyna and Nadsyannia
and with position changes at the front and redeployment of troops in the Lemkivshchyna. All these events took
place in 1943—1944. Only deportees, who were displaced in 1951, are an exception, for them, in contrast to other resettled
persons, the central story in the narratives is the deportation action.
Two ways of representing the experience of inter-ethnic conflict are singled out. The first is almost non-emotional list
of the injustices and misfortunes that the community has experienced. To another belong narratives, which are in many
cases fragmentary and full of dramatic emotions. These two ways may be indicative of psychological trauma and reluctance
to remember it, or of the post-memory. It is emphasized that many memories are the post-memory of persons, who
were deported in childhood, or were born in the families of displaced persons after deportation.
The representation of the deportations of 1944—1951 in the media space of Ukraine and Poland in 1990—2017 is
investigated. Resettlement actions are mainly the part of the regional historical memory. The memory of them is especially
strong in places of compact settlement, or in family environments of resettled persons. Increased media interest in
deportations appears on the eve of the anniversaries and is especially intense before round number dates, as, for example,
in the case of the 70th anniversary of Operation “Vistula”.
The relationship between different levels of identity, in particular regional (local) and national, is investigated. The
concept of small homeland is considered through the prism of collective memory. Certain universality of the process of
sacralization and idealization of the small homeland is confirmed. It is noted that similar processes occurred with the
memory in Polish society about the so-called “Kresy” (eastern borderlands, eastern regions of the Second Polish Republic
during the interwar period) or about the areas, which were lost by Germany after the war. The memory of the place of
birth, of childhood, of youth became the space wherein the home was introduced, after what it became the sacrum that
was the basis for constructing identity. It is established that the descendants of the deportees, as the materials of the conducted
surveys have shown, heard the stories of their relatives about the territory of Zakerzon and deportation. However,
the origin of the parents or family experience did not affect most of the children and grandchildren of the deportees. Only
for a part of the descendants, who grew up with traumatic stories, these lands became the so-called post-memory, built on
the emotional experience of someone else’s experience. This memory has become important not because of the feeling of
belonging to these territories, but because of the connection with relatives who came from Zakerzon.